The Effect of Character and Learning Motivation on Learning Achievment of Al-Qur'an Hadith Students of Madrasah Aliyah Attahiriyah Jakarta, Indonesia - Ika Kartika; Arman Paramansyah (Dinasti Publisher, 2025)
The background of this research is that the teaching of Al-Qur'an Hadith is still inefficient because learning methods and media treated ineffective, resulting in student character and learning motivation being considered not ideal. The purpose of this study was to determine the positive influence of student character on Learning achievement of the Qur'an Hadith, to resolve the positive control of learning motivation on Learning achievement of the Qur'an Hadith, and to determine the positive influence of student character on learning motivation. This study design uses quantitative research with the Partial Least Square (PLS) approach with Structural Equation Modeling (SEM). A sample of 150 students was determined using the Simple Random Sampling technique. The results showed that student character had a direct positive and significant effect on Learning achievement of the Qur'an Hadith, learning motivation had a straight positive and significant reaction on Learning achievement of the Qur'an Hadith, besides student character had a direct positive and significant effect on learning motivation.